4a(3x-0,5y)=..........ax-.......an
2k(3m-1,5n=....km-...kn
3s(2s+4t) =....s²+...st
-2x²(-5x-4)=...x³+...x²

2x(3y+...)=....+12x²
5t²(....-0,2rt)=t²-....
-½y(2y²+....)=....-4y
....-2ab²:8=2ab-....
kn(....-n)=-k²n-....
.....*(3xy-2t)=6x²y-=
½a(4a²b²-....)=...-a²
3t²+....:-6= -⅓

1

Odpowiedzi

2010-03-03T09:06:53+01:00
4a(3x-0,5y)=12ax-2ay
2k(3m-1,5n)=6km-3kn
3s(2s+4t) =6s²+12st
-2x²(-5x-4)=10x³+8x²

2x(3y+6x)=6xy+12x²
5t²(0,2-0,2rt)=t²-rt³
-½y(2y²+8)=-y³-4y
(16ab-2ab²):8=2ab-0,25ab²
kn(-k-n)=-k²n-kn²
2x*(3xy-2t)=6x²y-4tx
½a(4a²b²-2a)=2a³b²-a²
3t²+....:-6= -⅓ - nie wim co tu jest